Parental Perception and Practices Relating to Parent-Child Communication on Sexuality in Lagos, Nigeria - Olaoluwa Akinwale; Adeniyi Adeneye; David Omotola; Ogenna Manafa; Taiwo Idowu; Babatunde Adewale; Medinat Sulyman Sulyman; David Akande (Tehran University of Medical Sciences, 2009)
Objective: This study aimed at contributing to the promotion of positive communication between parents and children in order to help the children establish individual values and make sexually healthy decisions. Materials and method: Ninety six out of 300 in-school adolescents previously interviewed were selected for follow-up interview with their respective parents/guardians using a simple random sampling technique. Semi-structured questionnaires were administered on the parents/guardians after obtaining their informed consents. Results: Of the 93 respondents that freely discuss with their children, the frequencies were: regularly (68.8%); occasionally (28.0%); and (3.2%) could not recall.  More of those that discussed about sexuality issues were younger with a mean age of 45.5 years compared to 48.3 years for those who did not (χ2 = 40.91, df = 50, p < 0.05). Similarly, younger respondents perceived sexuality education more important than older respondents (χ2= 61.81, df = 75, p < 0.05). Very few discussed HIV/AIDS with their male children while none had such discussion with their female children. About one-quarter of the parents did not believe in children knowing about contraceptives, stating that such exposure is unnecessary because it will initiate the children into early sexual activities. This communication gap was more evident when about one-third of the respondents insisted they will not counsel their children about contraceptives. Conclusions: Parents should be assisted in developing specific knowledge and skills to support their adolescents' sexual decision making. Intervention programs should target particularly the older ones, who are usually not too comfortable in discussing issues relating to sexuality with their children.